Excessive use of medically important antimicrobials in food animals in Pakistan: a five-year surveillance survey. (13th December 2019) - Mohsin, Mashkoor; Van Boeckel, Thomas P.; Saleemi, Muhammad Kashif; Umair, Muhammad; Naseem, Muhammad Noman; He, Cheng; Khan, Ahrar; Laxminarayan, Ramanan
ABSTRACT: Demand for poultry meat is rising in low- and middle-countries, driving the expansion of large commercial farms where antimicrobials are used as surrogates for hygiene, good nutrition. This routine use of antimicrobials in animal production facilitates the emergence and spread of antibiotic-resistant pathogens. Despite potentially serious consequences for the animal industry, few studies have documented trends in antimicrobial use (AMU) at the farm-level in low- and middle-income countries. The objective of this study was to estimate AMU in a broiler chicken farm in Pakistan over a five-year period and to extrapolate national AMU in commercial broiler farming. Between 2013 and 2017, we monitored AMU in 30 flocks from a commercial broiler farm in Punjab, the most populous province of Pakistan. The amount of antimicrobials administered was calculated in milligram/population unit of the final flock weight (mg/fPU) and in used daily dose (UDD). The annual on-farm antimicrobial use was 250.84 mg of active ingredient per kilogram of the final flock weight. This consumption intensity exceeds the amount of antimicrobial used per kilogram of chicken of all countries in the world except China. Measured in mg per kg of final flock weight or population unit (fPU), medically important drugs such as colistin (31.39 mg/fPU), tylosin (41.71 mg/fPU), doxycycline (81.81 mg/fPU), and enrofloxacin (26.19 mg/fPU) were the most frequently used antimicrobials for prophylactic or therapeutic use. Lincomycin was the most frequently used antimicrobial used in-feed (29.09 mg/fPU). Our findings suggest that the annual consumption of antimicrobials in the broiler sector in Pakistan could be as high as 568 tons. This alarmingly high consumption estimate is the first baseline study on antimicrobial use in animals in Pakistan. Our findings call for immediate actions to reduce antimicrobial use in Pakistan, and countries with comparable farming practices.